Methods of Improving Physical and Mechanical Properties of Light Concrete on the Basis of Chemical Additives - Abduraxmanov Abduxokim Abduvaxobovich (Zien Journals, 2022)
The rapid development of the global construction industry and rising prices for fuel and energy carriers lead to the need to create and implement resource and energy-saving technologies in the production of building materials and products.In this regard, the use of new types of environmentally friendly materials in the field of building materials, the effective use of energy-saving technologies, the improvement of new building materials and their existing technology, thereby improving the physico-mechanical and physicochemical properties of concrete and concrete mix takes over.
Keywords: masonry; material drying; vermiculite concrete; concrete